Regulation of adipocyte differentiation and lipid metabolism by novel synthetic chromenes exploring anti-obesity and broader therapeutic potential - Kewalin Inthanon; Natthawut Wong-a-nan; Srisulak Dheeranupattana; Andres Garcia Guerra; Neal M. Davies; Chatchai Kesornpun; Sasithorn Sangher; Prasat Kittakoop (Scientific Reports)
Abstract Obesity poses a significant global health challenge, necessitating the search for novel therapeutic agents to address this epidemic. Chromenes, known for their diverse bioactivities, hold promise as potential anti-obesity compounds, yet research in this area remains limited. This pioneering study represents the first exploration of synthetic chromenes as potential anti-obesity agents, unveiling the underlying molecular pathways governing adipogenesis and lipolysis. Twenty-nine chromenes were synthesized using green chemistry approaches, resulting in five novel compounds: 1, 2, 3, 4, and 5. Among them, 14 chromenes demonstrated a lack of toxicity to pre-adipocytes (PAs) and mature adipocytes (MAs) of 3T3-L1 cells. The anti-adipogenesis and lipolysis enhancement potential of these non-toxic 14 chromenes were comprehensively evaluated using Oil Red O staining technique, LDH activity measurement, and glycerol release assays. Notably, 4, 5, 21 and 25 exhibited remarkable efficacy in reducing intracellular lipid accumulation without inducing cellular stress or cell death. Molecular analysis revealed significant alterations in the expression of key transcription factors involved in adipogenesis and lipid metabolism, including PPARγ, C/EBPα, ADD-1, Pref-1, IRS-1, GLUT-4, adiponectin, FAS, aP2, ATGL, and HSL. This suggests their potential role in anti-adipogenesis. Additionally, the treatments with 4 and 25 showed potential for enhancing lipolysis, providing further evidence of their anti-obesity properties. This study presents several promising prospects for the development of synthetic chromenes as potential anti-obesity agents, opening new avenues for drug discovery and benefitting individuals worldwide in addressing obesity-related challenges to human health. In addition, predictive in silico modeling was performed on the identified candidate chromenes. This modeling provides prospective anti-HIV activity, pharmacokinetic, metabolism, and permeability data, setting the groundwork for further investigation into these potential new chemical entities.